Efecto citotóxico del extracto acuoso de hojas de Annona cherimola en una línea celular de cáncer de colon humano en medio de cultivo con pH neutro. - Peralta Armijos, Jéssica Yajaira (2016)
Cancer is a disease that can appear anywhere on the body, is defined as a process of uncontrolled growth and spread of cells. The growths often invade surrounding tissue and can metastasize to distant sites. One type of cancer is most often diagnosed with colon cancer, which is a condition of the large intestine that threatens the life of the person who has it. The aim of this investigation was to verify the cytotoxic activity of the aqueous extract of leaves Anonna cherimola in a cell line of human colon cancer (RKO) in culture medium with neutral pH. This study is experimental design - Prospective which took place in the city of Loja, in the laboratories of Biotechnology of the National University of Loja, cells of human colon cancer was grown with the aqueous leaf extract of Annona cherimola in a culture medium with neutral pH, in this study techniques are used to assess cell proliferation through cell count in a Neubauer chamber and cell viability determined by performing the respective counts of live cells and dead cells at certain time periods. Through this study it was determined that aqueous leaf extract of Annona cherimola produced 60.9% cell death at 72 hours incubation in the concentrate and 55.5% cell death at 1:10 dilution in 72 hours of incubation and proliferation of 83.2% at 36 hours and 36.7% after 72 hours incubation in the concentrate. KEY WORDS: cancer, colon, Anonna cherimola, aqueous extract, cell proliferation, cell viability.